CONCENTRATION OF TOXIC METALS IN BENTHIC ORGANISMS OFF BOMBAY COAST - ABIDI, S.A.H.; VARSHNEY, P K (Journal of Indian Fisheries Association, 2015)
Concentration of toxic metals namely Zn, Cu, Fe, Cd and Pb in the marine benthos offBombay coast was estimated. Maximum concentration of Zn, Fe and Pb was from theorganisms of Thana Creek. Higher concentration of Cu was encountered in benthic organismsoffVersova. Cd was detected in some organisms and was maximum in the organisms coll